2016
DOI: 10.1016/j.ultsonch.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high intensity ultrasound on transglutaminase-catalyzed soy protein isolate cold set gel

Abstract: The effects of high intensity ultrasound (HIU, 105-110 W/cm(2) for 5 or 40 min) pre-treatment of soy protein isolate (SPI) on the physicochemical properties of ensuing transglutaminase-catalyzed soy protein isolate cold set gel (TSCG) were investigated in this study. The gel strength of TSCG increased remarkably from 34.5 to 207.1 g for TSCG produced from SPI with 40 min HIU pre-treatment. Moreover, gel yield and water holding capacity also increased after HIU pre-treatments. Scanning electron microscopy showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(58 citation statements)
references
References 44 publications
4
51
0
Order By: Relevance
“…Calcium-independent microbial transglutaminase (MTG) is an enzyme that can catalyse intra-and interacyl transfer reactions between the c-carboxyamide group of glutamine residues and the e-amino group of lysine residues in peptides or proteins (Zhang et al, 2016). As a result, e-(c-glutamyl)-lysine isopeptide cross-linking is formed (Gaspar & de Goes Favoni, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium-independent microbial transglutaminase (MTG) is an enzyme that can catalyse intra-and interacyl transfer reactions between the c-carboxyamide group of glutamine residues and the e-amino group of lysine residues in peptides or proteins (Zhang et al, 2016). As a result, e-(c-glutamyl)-lysine isopeptide cross-linking is formed (Gaspar & de Goes Favoni, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With growing demand for functional agents in various food products, the application of high‐intensity ultrasound to modify certain functional properties of whey proteins as an alternative to traditional methods is a hot topic of study in food science technologies. Up to now, several studies (Hu et al ., ,b, ; Jambrak et al ., ; Sun et al ., ; Zhang et al ., ; O'Sullivan et al ., ; Xiong et al ., ; Zhou et al ., ) have shown that high‐intensity ultrasound can change physical and functional properties of several food proteins, including increasing surface hydrophobicity, emulsifying activity, emulsion stability and protein solubility, reducing viscosity, and improving gelling properties and foaming capacity. Therefore, we hypothesise that high‐intensity ultrasound has similar positive effects on WPI proteins.…”
Section: Introductionmentioning
confidence: 99%
“…High intensity ultrasound is considered to be a promising technique that is relatively economical and easy to operate. Several studies have shown that ultrasound treatment can change the gelation properties of different food proteins [ 33 36 ], including whey protein [ 37 ]. Therefore, the objective of the current research was to generate a WPI based lutein loaded nano-emulsion system using ultra intensity ultrasound and evaluate its stability at different storage conditions.…”
Section: Introductionmentioning
confidence: 99%